"A Noble Class of Old Maids": Surrogate Motherhood, Sibling Support, and Self-Sufficiency in the Nineteenth-Century White, Southern Family. (October 2016) - Molloy, Marie S.
Single, white, slaveholding women in the nineteenth-century south performed key roles within the southern family: as the "family" caregiver, maiden aunt, and in support of siblings during times of adversity, particularly during the tumultuous years of the Civil War. These women, far from being a drain on the southern family as has previously been argued, were frequently harbingers of social change and strong forces that held families together in tough social, economic, and demographic times. Through their roles in the family, and increasingly outside of it, these women gained special recognition for their contribution to the family unit, and increasingly to the community, thus enabling them to carve out new identities as capable, independent, and reliable women who dovetailed with the rise of the "Cult of Single Blessedness." These more visible "public" roles slowly challenged preconceived ideas on female singleness, gaining single women external praise for their contributions, which led to a new recognition of singleness, and a gradual reconstruction of the boundaries of "true womanhood."